Major accomplishments in composite materials and sandwich structures : an anthology of ONR sponsored research - Daniel, Isaac M.; Gdoutos, E. E., 1948-; Rajapakse, Y. (Dordrecht (Germany) ; New York : Springer, 2009)
"This book represents a collection of major research contributions over the last decade in the area of composite materials and sandwich structures supported by the USA Office of Naval Research under the directorship of Dr. Yapa D. S. Rajapaske."--P. [4] of cover.
Includes bibliographical references and author index.
Keywords: Composite materials; Sandwich construction